Asuhan Keperawatan Gerontik Pada Pasien Dengan Diabetes Mellitus Dipanti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Alya Fajriza Candra; Sandra Dewi; Hasmita .; Kheniva Diah Anggita (CV. ITTC INDONESIA, 2026)
Based on the International Diabetes Federation Data in 2021, more than 500 million people worldwide, precisely 537 million, suffer from diabetes. The percentage of the incidence of Diabetes Mellitus in Indonesia according to the Indonesian Health Survey is 1.7% with a total of 877,531 sufferers and the incidence of Diabetes Mellitus in West Sumatra shows 1.2% with a total of 18,138 sufferers. Diabetes Mellitus is a chronic disease caused by the body's inability to produce the hormone insulin or due to ineffective use of insulin production. This is characterized by high blood sugar levels. This case study aims to implement nursing care for Mr. E with Diabetes Mellitus at the Sabai Nan Aluih Sicincin Social Home for the Elderly, Padang Pariaman Regency. The method used is a nursing process approach consisting of assessment, nursing diagnosis, intervention, implementation, evaluation, and documentation. The research design used is descriptive with a case study approach. Data were obtained through interviews and observations. The results of the study are Mr. Mr. E, 73, experienced itching on his palms, with peeling skin, and reported taking Metformin 850 mg twice daily. Three diagnoses were diagnosed in Mr. E's case: unstable blood glucose levels, impaired skin/tissue integrity, and risk of falls. After a 5-day evaluation, the stability of blood glucose levels increased, skin integrity improved, and the fall rate decreased. It can be concluded that comprehensive geriatric nursing care can increase the independence of the elderly in caring for their physical condition independently.